Updated planetary mass constraints of the young V1298 tau system using MAROON-X - Sikora, James; Rowe, Jason; Barat, Saugata; Bean, Jacob L.; Brady, Madison; Désert, Jean-Michel; Feinstein, Adina D.; Gilbert, Emily A.; Henry, Gregory; Kasper, David; Lizotte, Déreck-Alexandre; Matesic, Michael R. B.; et al. (The astronomical journal, 2023)
The early K-type T-Tauri star, V1298 Tau (V = 10 mag, age ≈ 20-30 Myr) hosts four transiting planets with radii ranging from 4.9 to 9.6 R ⊕. The three inner planets have orbital periods of ≈8-24 days while the outer planet’s period is poorly constrained by single transits observed with K2 and the Transiting Exoplanet Survey Satellite (TESS). Planets b, c, and d are proto-sub-Neptunes that may be undergoing significant mass loss. Depending on the stellar activity and planet masses, they are expected to evolve into super-Earths/sub-Neptunes that bound the radius valley. Here we present results of a joint transit and radial velocity (RV) modeling analysis, which includes recently obtained TESS photometry and MAROON-X RV measurements. Assuming circular orbits, we obtain a low-significance (≈2σ) RV detection of planet c, implying a mass of and a conservative 2σ upper limit of <39 M ⊕. For planets b and d, we derive 2σ upper limits of M b < 159 M ⊕ and M d < 41 M ⊕, respectively. For planet e, plausible discrete periods of P e > 55.4 days are ruled out at the 3σ level while seven solutions with 43.3 < P e/d < 55.4 are consistent with the most probable 46.768131 ± 000076 days solution within 3σ. Adopting the most probable solution yields a 2.6σ RV detection with a mass of 0.66 ± 0.26 M Jup. Comparing the updated mass and radius constraints with planetary evolution and interior structure models shows that planets b, d, and e are consistent with predictions for young gas-rich planets and that planet c is consistent with having a water-rich core with a substantial (∼5% by mass) H2 envelope.